Performance improvement study of a relativistic magnetron using MAGIC-3D - Maurya S.; Singh V.V.P.; Jain P.K. (My University, 2025)
A three dimensional particle-in-cell (PIC) code, MAGIC3D, is used to examine the performance improvement in a relativistic magnetron by perturbing technique. Asymmetrical metal rods of different length have been used to perturb the magnetic field in the annular sector of the resonant system. Enhancement up to 45% in the radiated output power has been obtained in the perturbed magnetic field case over the unperturbed one. It has also been found in the simulation that oscillation start up time is reduced by 16 %, and the amplitude of the nearest competing mode goes down 9dB compared to unperturbed case. Perturbed magnetic field also reduces the end caps current improving the efficiency. © 2011 IEEE.